(untitled) (Universal International Scientific Journal, 2026)
This article discusses the content of personnel motivation in educational institutions. The system of personnel motivation in educational institutions differs from other areas in its versatility, social orientation and long-term nature of the results of activities. In the effective organization of this system, it is important to take into account the fact that the personnel structure consists of different categories.